Shear Strength and Durability Behaviors of Compacted Weathered Clay Shale Mixture Using Portland Cement - Simatupang, Pintor Tua; Idrus M. Alatas; Ayu K. Redyananda; Eko A. Purnomo (Journal of the Civil Engineering Forum, 2022)
The use of weathered clay shale often has the potential to cause geotechnical problems as an embankment material, especially slope failures. In order for weathered clay shale to be used as embankment material, the weathered clay shale must be mixed with other materials. An example of a widely used mix is a mix with a Portland cement (PC). In general, this mixture will increase the shear strength of the embankment material. In addition to shear strength, it is very important to investigate whether the material mixture is susceptible to durability. Therefore, this study aims to evaluate the shear strength and durability behaviors of weathered clay shale mixture, using PC. The percentage of this cement was varied and did not exceed 20%, with the mixing material also compacted based on Proctor Standard procedure. This test included the determination of shear strength and durability index at the smaller and larger (dry and wet sides) than optimum moisture content (OMC). Shear strength and durability index were determined by Triaxial and slake durability index tests, respectively. The results showed that the weathered clay mixture with 10% PC and 8% larger OMC led to an increase in the normalized shear strength (∆σ/σ) and durability index at approximately 300% and 24%, respectively, compared to the original clay shale. This indicated that the optimum shear strength and durability of this shale mixture were highly observed at 10% PC and 8% larger OMC (wet side). This verified also although the durability index increased by 97% with the addition of 20% PC, whose utilization was found to be unrealistic